SHARK FIN RAYS-TECHNOLOGY OF EXTRACTION. - RAMACHANDRAN NAIR, K G; MADHAVAN, P (Fishery Technology, 2017)
A simple process is described for extraction of rays from shark fins. The process consists in treating the rays with acetic acid to soften the tissue, separation. of the rays by hand and drying. White fins yield almost double the quantity of rays compared to black fins.